1982
DOI: 10.1021/ja00373a059
|View full text |Cite
|
Sign up to set email alerts
|

Use of D-[13C6]glucose together with carbon-13-depleted glucose and homonuclear carbon-13 decoupling to identify the labeling pattern by this precursor of the "m-C7N" unit of geldanamycin

Abstract: and Infectious Diseases and by a Procter & Gamble Fellowship to M.P. (1981)(1982). We thank the Stable Isotopes Resource at Los Alamos Scientific Laboratories, jointly supported by the Energy Research and Development Administration and the Division of Research Resources, NIH (Grant No. 1 P07 RR-00962-01), for providing [l3C6]glucose and 13C-depleted glucose and the University of Illinois NSF Regional Instrumentation Facility (NSF CHE 79-16100) for 13C NMR spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…In this paper we report the results of studies on the biosynthesis of naphthomycin A that show that its formation probably follows a pathway similar to that previously demonstrated for rifarnycin S (1 1-13), geldanamycin (14,15), actamycin (9,16), and ansatrienin (13,17,18 …”
supporting
confidence: 60%
See 1 more Smart Citation
“…In this paper we report the results of studies on the biosynthesis of naphthomycin A that show that its formation probably follows a pathway similar to that previously demonstrated for rifarnycin S (1 1-13), geldanamycin (14,15), actamycin (9,16), and ansatrienin (13,17,18 …”
supporting
confidence: 60%
“…Thus the formation of 2 must branch ~, off from the miin pathway at an earlier stage. Another intriguing feature is the finding, in the cases of the mitomycins (37) geldanamycin (15) and ansatrienin A (38), that the nitrogen atom of the mC7N unit is attached to the carbon atom corresponding to C5, not C3, of a shikimate-equivalent moiety. The same conclusion is reached about the mC7N unit of 1 from the results of the [~-'~~~]~l~c e r o l experiment presented above.…”
Section: Resultsmentioning
confidence: 99%
“…Degradations of mitomycins derived from various labeled precursors indicated that the C-5-equivalent carbon carries the nitrogen. 21 Although this result was initially questioned when it was found that in pactamycin the C-3-equivalent carbon carries the nitrogen, 15 this turned out to be an anomaly, and further work by Rinehart et al 40 on geldanamycin soon confirmed Hornemann's conclusion from the mitomycin study. Subsequent work in other systems also confirmed the site of attachment of the nitrogen.…”
Section: Historymentioning
confidence: 99%
“…Gabaculine (5-amino-1,3-cyclohexadienelcarboxylic acid), a naturally occurring amino acid isolated from Streptomyces toyocaenis (56), is an irreversible inhibitor of many PLP-requiring aminotransferases (57). Rinehart et al (58) and Ganem (59) had, in fact, suggested that this compound might be an intermediate on the biosynthetic pathway to mC 7 N units. In view of the structural similarity of gabaculine and aminoDHS, we checked the effect of gabaculine on AHBA synthase.…”
Section: -Amino-5-hydroxybenzoic Acid Synthasementioning
confidence: 99%